1998
DOI: 10.3367/ufnr.0168.199805a.0481
|View full text |Cite
|
Sign up to set email alerts
|

The lightest scalar glueball

Abstract: Recently performed investigations of meson spectra allow us to determine the resonance structure for the waves IJ P C = 00 ++ , 10 ++ , 02 ++ , 12 ++ = IJ P = 1 2 0 + in the mass region up to 1900 MeV, thus establishing the meson multiplets 1 3 P0qq and 2 3 P0qq. Experimental data demonstrate that there are five scalar/isoscalar states in this mass region. Four of them are qq states, that is, members of the 1 3 P0qq and 2 3 P0qq nonets, while the fifth state is an extra one not accomodated by qq systematics; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 70 publications
(66 reference statements)
2
25
0
1
Order By: Relevance
“…A brief discussion concerning spin-orbit effects in both models is given in part C. In the last part of section III, we focus on the pseudoscalar and scalar mesons by adding the residual 't Hooft interaction which only acts for mesons with vanishing total angular momentum. There we will also comment on a set of K-matrix poles found by V. V. Anisovich and coworkers [22][23][24][43][44][45] by comparing to our results. Finally we give a summary and conclusion in section IV.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…A brief discussion concerning spin-orbit effects in both models is given in part C. In the last part of section III, we focus on the pseudoscalar and scalar mesons by adding the residual 't Hooft interaction which only acts for mesons with vanishing total angular momentum. There we will also comment on a set of K-matrix poles found by V. V. Anisovich and coworkers [22][23][24][43][44][45] by comparing to our results. Finally we give a summary and conclusion in section IV.…”
Section: Introductionmentioning
confidence: 52%
“…This effect was illustrated by carrying out the nonrelativistic reduction of both Dirac structures and it turned out that the Salpeter equation in model A reduces to the usual Schrödinger equation whereas in model B the negative energy components do not vanish even in this limit. By virtue of these observations one can conclude that any quark model should account for the correct treatment of relativistic effects not only in the calculations of deeply bound state masses (M ≪ m 1 + m 2 ) but also in the case of higher radial excitation states 16 There exists a second K-matrix solution for the 2 3 P0qq nonet: the authors in [22][23][24][43][44][45] find a third scalar isoscalar bare state between 1200-1600 MeV, the f bare 0 (1235 ± 50), which, instead of the f bare 0 (1600 ± 50), can also be used to complete the 2 3 P0qq nonet. So, one of the scalar isoscalar bare states in the mass region 1200-1600 MeV is superfluous for theqq classification and may be connected to the lightest scalar glueball.…”
Section: Discussionmentioning
confidence: 90%
“…Especially the real part of the mass shift is strongly affected by higherorder corrections. In a recent K-matrix analysis [51], as well as in a covariant quarkonium model [52], it is indeed also found that the bare state might be appreciably lower than the central resonance position for the K * 0 (1430). The K * 0 (727) singularity (23) does not have a direct relation to any of the states stemming from the confinement mechanism.…”
Section: (21)mentioning
confidence: 98%
“…Тому в цьому сенсi опис зв'язаних ґлюонiв може мало вiдрiзнятися вiд опису зв'язаних кваркiв. Опосередковано про це говорить схожiсть властивостей ґлюболiв i кварк-антикваркових систем [53][54][55][56][57]. Наявнiсть енерґетичного порога народження зв'язаних ґлюонiв приводить до того, що якщо енерґiя взаємодiї ґлюонiв у ґлюболi менша за цей порiг, то новi зв'язанi ґлюони народжуватися не зможуть i ми матимемо систему з фiксованою кiлькiстю частинок.…”
Section: квантування багаточастинкових полIвunclassified